Tiempo y espacio como ideología - Alfaro Vargas, Roy (2011)
This article analyzes the relationship of the categories of time and of space, as long as holder of the ideological process, since the alteration of these categories is what characterizes to such a process. That is to say, the divisions of this even dialectical categorial bears a characterization of the reality like something static. Also, it thinks about the timespatiality concept as a notion that re-establishes the dialectical unit of the categories of time and space, and that it allows the apprehension of the movement.